A Profound Membrane Reorganization Defines Susceptibility of Plasmodium falciparum Infected Red Blood Cells to Lysis by Granulysin and Perforin - Hernández-Castañeda, Maria Andrea; Lavergne, Marilyne; Casanova, Pierina; Nydegger, Bryan; Merten, Carla; Subramanian, Bibin Yesodha; Matthey, Patricia; Lannes, Nils; Mantel, Pierre-Yves; Walch, Michael (Frontiers in Immunology, 2021)
Malaria remains one of the most serious health problems in developing countries. The causative agent of malaria, Plasmodium spp., have a complex life cycle involving multiple developmental stages as well as different morphological, biochemical and metabolic requirements. We recently found that gd T cells control parasite growth using pore-forming proteins to deliver their cytotoxic proteases, the granzymes, into blood residing parasites. Here, we follow up on the molecular mechanisms of parasite growth inhibition by human pore-forming proteins. We confirm that Plasmodium falciparum infection efficiently depletes the red blood cells of cholesterol, which renders the parasite surrounding membranes susceptible to lysis by prokaryotic membrane disrupting proteins, such as lymphocytic granulysin or the human cathelicidin LL-37. Interestingly, not the cholesterol depletion but rather the simultaneous exposure of phosphatidylserine, a negatively charged phospholipid, triggers resistance of late stage parasitized red blood cells towards the eukaryotic pore forming protein perforin. Overall, by revealing the molecular events we establish here a pathogen-host interaction that involves host cell membrane remodeling that defines the susceptibility towards cytolytic molecules.